How to Bomb Cancer? - Zięcik, Adam J.; Kaczmarek, Monika (ACADEMIA. The magazine of the Polish Academy of Sciences, 2004)
Most peptide hormones bind to specific molecules on a cell's surface. Biotechnology offers some clues about how we can use this "key-lock" interaction to defeat cancer.